SOLUTION OF REMOTE MANAGEMENT SYSTEM FOR COMPUTER NETWORK INFRASTRUCTURE WITH INTEGRATED NETBOX’ - Kaklauskas, Liudvikas; Pilypas, Irmantas (PROFESSIONAL STUDIES: Theory And Practice, 2025)
The purpose of the research is to create an automated switch configuration management system using the NetBox platform. A Python program developed for data processing integrated into NetBox. System objects were be linked by Django relational relationships using REST API methods. An interaction model of system components was implemented using SSH Paramiko and Netmiko libraries. The integration points of NetBox platform REST API were supplemented with seven switch port configuration methods using Token authentication. Testing of the system showed that the port parameters data was successfully transferred in an average of 135 milliseconds. By research established that SSH protocol library Netmiko is better compatible with different switch models.